2023
DOI: 10.3390/ijerph20020948
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Impact of Early Stages of the COVID-19 Pandemic on Individuals with Pre-Existing Mental Disorders: A Systematic Review of Longitudinal Research

Abstract: In view of disease-related threats, containment measures, and disrupted healthcare, individuals with pre-existing mental illness might be vulnerable to adverse effects of the COVID-19 pandemic. Previous reviews indicated increased mental distress, with limited information on peri-pandemic changes. In this systematic review, we aimed to identify longitudinal research investigating pre- to peri-pandemic and/or peri-pandemic changes of mental health in patients, focusing on the early phase and considering specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 97 publications
1
11
0
Order By: Relevance
“…The COVID‐19 pandemic may have had little impact on problematic eating symptoms in people with preexisting eating disorders; however, the evidence is very uncertain. Our findings align with a past narrative review 20 of longitudinal studies, but are disparate from Devoe et al . 's systematic review, 60 which concluded that eating disorder symptoms increased during the pandemic.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The COVID‐19 pandemic may have had little impact on problematic eating symptoms in people with preexisting eating disorders; however, the evidence is very uncertain. Our findings align with a past narrative review 20 of longitudinal studies, but are disparate from Devoe et al . 's systematic review, 60 which concluded that eating disorder symptoms increased during the pandemic.…”
Section: Discussionsupporting
confidence: 82%
“…Symptom reactivation may explain the high prevalence of anxiety (26%) and depression (19%) reported in people with preexisting psychiatric disorders during the first 5 months of the COVID‐19 pandemic 19 . Third, previous reviews of eating disorder populations have found conflicting results, possibly due to study design differences 12,20 . A narrative synthesis of longitudinal studies found that mental health symptoms probably improved for people with eating disorders, 20 whereas a meta‐analysis that combined study designs showed that 65% of patients with eating disorders reported worse symptoms during the pandemic 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the meta-analysis was inappropriate due to the lack of metrics reported in < 3 studies, a vote-counting model was conducted according to previous studies, with the direction of effect [30][31][32]. The model followed the Cochrane and Synthesis without meta-analysis (SWiM) reporting guidelines [33,34].…”
Section: Data Analysis and Levels Of Evidencementioning
confidence: 99%
“…Although the COVID-19 pandemic undeniably impacted mental health worldwide, it is important to critically examine the narrative that the pandemic precipitated a uniformly dramatic increase in mental health crises. The longitudinal data on pandemic-related changes to mental health have been heterogeneous, with various studies 4 demonstrating resilience and even improvements in mental health measures, even among vulnerable groups. This heterogeneity of outcomes, ranging from positive to negative, is often hidden in public and scientific discussions.…”
mentioning
confidence: 99%